Design of a Mobile Phone Sales System Website at Vivo Store - Auliana, Sigit; Pratama, Gelard Untirtha; Permana, Basuki Rakhim Setya; Sunardi, Sunardi; Firmansyah, Oki (ARRUS Journal of Engineering and Technology, 2024)
One aspect highlighted is the importance of the internet in commerce, particularly e-commerce, which connects sellers and buyers without limitations of time and place. Websites serve as crucial instruments to facilitate the ordering and sales processes, enabling access to information anytime and anywhere, clarifying company operations, and enhancing customer convenience in placing orders. This study aims to analyze the development of the Vivo Store mobile phone sales website and evaluate its effectiveness. The website aims to broaden marketing reach and enhance customer accessibility in placing orders. The research is expected to contribute by optimizing the mobile phone sales process at Vivo Store through a waterfall methodology-designed website. This website aims to simplify purchasing for customers without the need to visit physical stores and assist employees in data management through a database. The results show that the development of the mobile phone sales website at Vivo Store using the waterfall method has been successfully completed. This website allows customers to make purchases online without visiting physical stores and assists employees in managing available units through a database. The development of the mobile phone sales website using the waterfall method is a successful step that benefits Vivo Store in optimizing their e-commerce business. This research provides valuable contributions to infrmation technology and marketing strategies in the current era of online commerce. The analysis used is to study a number of information about sensory perception learning and collect materials related to sensory perception that will be used in this application program. Such as searching and editing images. The aim is to help beginners learn about sensory perception so that it can provide convenience in learning, without having to adjust the time of learning. Then an application program was made to recognize sensory perception. Sensory perception learning through this learning media is a useful media for helping to recognize sensory perception, through sensory perception learning media this makes an interesting and effective thing because it is designed with images, animations, and sounds that support the atmosphere of learning.